Clearing the detail coefficient of 2-D DWT Architecture based on Lifting scheme of 5/3 and 9/7 Filters - Dhafer Al-layla (College of Education for Pure Sciences, 1999)
Abstract In This paper, An efficient architecture for the implementation of two dimensional discrete wavelet transform based on lifting scheme for two types of JPEG2000 filters (5/3 and 9/7 filter) are proposed. The pipelining method is applied in the proposed architecture to design multilevel (three-level) architecture for both direction (forward and inverse) transform. After that, the proposed architecture is used to study the effect of clearing the detail coefficients HH, HL and LH sub-band images into the quality of reconstruction image, the proposed one-level two dimensional discrete wavelet transform architecture (one-level 2-D DWT) is built by using the one dimensional discrete wavelet transform (1-D DWT) only,then by using the 1-D DWT as basic element, the architecture are developed to built the three-level two dimensional discrete wavelet transform module (three-level 2-D DWT). The Matlab was used to simulate the proposed architectures and measure the quality of image by using the signal to Noise Ratio (SNR).